Linguistic Devices Used to Persuade and Manipulate Audiences of Political Discourse in the 2020 US Presidential Election - Fadhli, Ridhatul; Rosita, Nur (English Language and Literature, 2023)
This study is concerned with the linguistic devices used to persuade and manipulate audiences of political discourse in the 2020 US Presidential election. This study focused on Donald Trump's and Joe Biden's rhetorical and framing strategies in their speech and debate. A qualitative method was used to conduct the study to analyze the data. The study aimed to find the rhetorical and framing strategies of Donald Trump and Joe Biden and to find how they persuade and manipulate audiences of the political discourse. The findings reveal that the rhetorical strategy, Pathos, or the appeal to emotions, was utilized the most by Donald Trump compared to a more balanced use of all rhetorical strategies by Joe Biden. At the same time, logos were focused more on debates for both candidates. For framing strategies, both candidates utilized emphasis the most to stress the importance of an issue or to concentrate on a message. According to the analysis, Donald Trump mainly used persuasive language, which can be seen by referencing "patriots" several times to evoke a sense of unity, which is different compared to his debates, where he is very manipulative in using statistics and facts that are not fully referenced and an abundance of straight lies. This can be seen when he claimed that he cut "drug prices," which is false. Joe Biden used a persuasive strategy by referencing history and events such as "Charlottesville".